A modified carbon-based negative electrode material and its preparation method and application
By using a modified carbon-based negative electrode material in sodium ion batteries and using a combined structure of microporous carbon matrix, graphene polymerization layer and mesoporous carbon layer, the existing carbon-based materials have been solved, and the capacity of the existing carbon-based materials in sodium ion batteries is achieved, achieving higher cycle stability and capacity.
Patent Information
- Application Number
- CN202411489811.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The application of existing carbon-based materials in sodium ion batteries has problems of reduced capacity and poor circulation performance, mainly due to the structural damage caused by the restricted embedding of sodium ions and volume changes.
A modified carbon-based negative electrode material is used, which consists of a microporous carbon matrix, a graphene polymerization layer and a mesoporous carbon layer. The graphene polymerization layer improves conductivity and structural stability through the composite skeleton and carbonized layer, while the mesoporous carbon layer enhances the permeability of the electrolyte and the transfer rate of sodium ions.
The modified carbon-based anode material significantly improves the cycling stability and capacity of sodium ion batteries by providing more sodium ion intercalation sites, alleviating volume changes and improving conductivity.
Smart Images

Figure CN119008940B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a modified carbon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] With the growth of global energy demand and dependence on renewable energy, the development of energy storage technology has become crucial. Among various energy storage technologies, lithium-ion batteries have dominated the energy storage market due to their high energy density, long cycle life and good safety. However, the limited and uneven distribution of lithium resources restrict the development of lithium-ion batteries. Since sodium and lithium are in the same main group in the periodic table, the two metal elements have similar chemical properties, and sodium resources are abundant, low-cost and widely distributed, the use of sodium-ion batteries to replace lithium-ion batteries has great development potential.
[0003] Since the radius of sodium ions is about 55% larger than that of lithium ions, the volume of the negative electrode material changes greatly during the insertion and deinsertion of sodium ions, which can easily cause structural damage and degradation of the electrochemical properties of the negative electrode material. Therefore, the selection of suitable negative electrode materials is a key factor in improving the performance of sodium ion batteries. Currently, the commonly used negative electrode materials mainly include carbon-based materials, metal oxide materials, alloy materials, etc. Among them, carbon-based materials have better conductivity, lower cost and better cycle stability. Therefore, different forms of carbon materials such as graphite, hard carbon, soft carbon and graphene have been widely studied in sodium ion batteries.
[0004] However, the direct application of carbon-based materials in sodium-ion batteries often shows problems such as decreased capacity and low cycle performance. This is because the embedding of sodium ions in the carbon-based layer is limited, and the performance of carbon-based materials in sodium-ion batteries is significantly worse than that in lithium-ion batteries. Therefore, in order to improve the electrochemical performance of carbon-based materials in sodium-ion batteries, carbon-based materials are usually doped with elements such as nitrogen, boron and phosphorus, which can increase the surface active sites and improve the sodium storage capacity. However, the doping process requires more complicated processes and high costs. In addition, the entry of impurities during the doping process will destroy the interlayer structure of the original carbon-based material, thereby affecting the cycle stability. Therefore, there is an urgent need to provide a solution to improve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a modified carbon-based negative electrode material and a preparation method and application thereof.
[0006] In the first aspect, the present invention provides a modified carbon-based negative electrode material, comprising a microporous carbon matrix and a graphene polymerization layer and a mesoporous carbon layer sequentially formed on the outside of the microporous carbon matrix, and the graphene polymerization layer comprises a composite skeleton and a carbonized layer polymerized and carbonized on the surface of the composite skeleton, and the composite skeleton is formed by a composite of graphene and molybdenum sulfide.
[0007] The modified carbon-based negative electrode material provided by the present invention adopts a microporous carbon matrix as a core structure, which can provide a large number of active sites for the embedding and de-embedding of sodium ions, and its disordered structure helps to alleviate the volume change during the charging and discharging process, which is beneficial to improving the cycle stability of the battery. In addition, the graphene polymer layer provides an extremely conductive interface buffering effect, which can simultaneously absorb and disperse the stress of the microporous carbon matrix during the volume expansion process, avoid the collapse of the overall structure of the negative electrode material, and is beneficial to extending the service life of the negative electrode material. The mesoporous carbon layer can improve the permeability of the electrolyte in the negative electrode material, improve the transmission rate of sodium ions, and provide additional sodium ion embedding sites, which is beneficial to improving the capacity. In addition, a stable external framework can be formed to support the structure of the overall negative electrode material.
[0008] At the same time, the composite skeleton plays a supporting role in the graphene polymerization layer, and can also serve as a connecting network to connect the microporous carbon matrix and the mesoporous carbon layer, thereby effectively reducing the sodium ion transmission resistance and increasing the sodium ion transmission rate. In addition, the composite skeleton can improve the flexibility of the composite skeleton after the graphene and molybdenum sulfide are composited, and the adaptability of the graphene polymerization layer to the volume changes of the microporous carbon matrix and the mesoporous carbon layer and its own structural stability are improved. Furthermore, the carbonized layer polymerized and carbonized on the surface of the composite skeleton can improve the structural stability of molybdenum sulfide and graphene, forming a doped structure of graphene, molybdenum sulfide and carbonized layer, and can also form a composite structure with a repair mechanism in the negative electrode material, thereby reducing the micro cracks of the composite skeleton and effectively extending the service life and cycle stability of the negative electrode material.
[0009] In a second aspect, the present invention provides a method for preparing a modified carbon-based negative electrode material, comprising: subjecting a microporous carbon matrix to a hydrothermal reaction with nanographene in a sulfur-molybdenum mixed solution and separating and drying to obtain a modified precursor; polymerizing a polymerization monomer on the surface of the modified precursor under the action of an initiator and separating and carbonizing it, and then compounding it with mesoporous carbon to obtain a modified carbon-based negative electrode material.
[0010] The preparation method provided by the present invention is to subject a microporous carbon matrix, nano-graphene and a sulfur-molybdenum mixed liquid to a hydrothermal reaction. Since there are multiple active sites on the surface of the microporous carbon matrix, the nano-graphene can be attached to the surface of the microporous carbon matrix to form a basic skeleton. At the same time, nano-molybdenum sulfide is generated during the hydrothermal reaction and attached to the basic skeleton. In addition, a laminated composite structure of "graphene-nano-molybdenum sulfide" is continuously formed during the hydrothermal reaction, and the composite structure can form a preliminarily solidified composite skeleton after drying.
[0011] In addition, under the action of the initiator, the polymerization monomers can be polymerized in situ on the surface of the composite skeleton, and the formed polymerization layer structure is uniform and dense, so that the composite skeleton can be encapsulated after carbonization treatment, and at the same time, the polymerization layer can be prevented from blocking the pore structure within the composite skeleton. After being compounded with mesoporous carbon, a layer of mesoporous carbon structure can be wrapped on the outside of the overall structure, thereby effectively improving the performance of the negative electrode material.
[0012] Optionally, the following steps are included:
[0013] Putting the microporous carbon matrix and nanographene into a sulfur-molybdenum mixed liquid to prepare a mixed suspension;
[0014] The mixed suspension is separated after hydrothermal reaction and dried at 600-700° C. to obtain a modified precursor;
[0015] The modified precursor is mixed with the polymerizable monomer, and then in situ polymerized under the action of an initiator, and then separated and carbonized to obtain a modified intermediate;
[0016] The modified intermediate is mixed in a mesoporous carbon suspension, and then separated and dried to obtain a modified carbon-based negative electrode material.
[0017] Optionally, the microporous carbon matrix is surface activated by using a nitrogen-containing active agent; wherein the nitrogen-containing active agent includes at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, and lauryldimethylamine oxide.
[0018] Optionally, the mass ratio of the microporous carbon matrix to the nanographene is 1:(0.5-0.6).
[0019] Optionally, the particle size of the microporous carbon matrix is 500-800 nm.
[0020] Optionally, the particle size of the nanographene is 200-300 nm.
[0021] Optionally, the solutes in the sulfur-molybdenum mixed solution include at least thiourea and sodium molybdate.
[0022] Optionally, the molar ratio of sulfur element to molybdenum element in the sulfur-molybdenum mixed solution is 2:(1-2).
[0023] Optionally, the mass ratio of nanographene to sulfur element in the mixed suspension is 1:(1-1.5).
[0024] Optionally, the solid-liquid ratio in the mixed suspension is 0.1-0.2 g / mL.
[0025] Optionally, the microporous carbon matrix and nanographene are ground and premixed and then added into the sulfur-molybdenum mixed solution.
[0026] Optionally, after the microporous carbon matrix and nanographene are put into the sulfur-molybdenum mixed solution, a mixed suspension is prepared under physical dispersion, and the physical dispersion includes at least one of ultrasonic dispersion, oscillation dispersion, and stirring dispersion.
[0027] Optionally, the mixed suspension is incubated at 40-50°C.
[0028] Optionally, the pH of the mixed suspension is adjusted to 6-7.
[0029] Optionally, the mixed suspension is subjected to a hydrothermal reaction at 200-220°C.
[0030] Optionally, the mixed suspension is subjected to hydrothermal reaction for 18-24 hours.
[0031] Optionally, the mixed suspension is subjected to a hydrothermal reaction at 3-5 MPa.
[0032] Optionally, an organic ligand is also dissolved in the mixed suspension, and the organic ligand includes 2-(5-bromo-2-pyridyl azo)-5-(diethylamino)phenol and hydroxylamine.
[0033] Optionally, the mixed suspension is subjected to a hydrothermal reaction and then cooled to 50-70° C. before separation.
[0034] Optionally, when the mixed suspension is subjected to a hydrothermal reaction and then separated, the separation method includes one of filtration separation and suction filtration separation.
[0035] Optionally, after the mixed suspension is subjected to hydrothermal reaction and separated, deionized water and anhydrous ethanol are used for cyclic washing.
[0036] Optionally, the modified precursor is dried at 600-700° C. in a vacuum environment.
[0037] Optionally, the modified precursor is prepared by drying at 600-700° C. for 3-5 h.
[0038] Optionally, after the mixed suspension is subjected to a hydrothermal reaction and separated, the separated solid is heated to 600-700° C. at a rate of 1-10° C. / min.
[0039] Optionally, the mass ratio of the modified precursor to the polymerizable monomer is 1:(0.4-0.5).
[0040] Optionally, the polymerizable monomer includes at least one of pyrrole, aniline, thiophene and acrylonitrile.
[0041] Optionally, the initiator includes at least one of ammonium persulfate, azobisisobutyronitrile, and dibenzoyl peroxide.
[0042] Optionally, the mass ratio of the initiator to the polymerization monomer is (0.1-5):100.
[0043] Optionally, after the polymerizable monomers are dissolved to prepare a polymer solution, the modified precursor is mixed and dispersed in the polymer solution.
[0044] Optionally, the polymerization monomer is polymerized in situ on the surface of the modified precursor under the action of an initiator at 40-50°C.
[0045] Optionally, after in-situ polymerization under the action of an initiator and separation, carbonization is performed at 700-800° C. to obtain a modified intermediate.
[0046] Optionally, the liquid environment in the mesoporous carbon suspension includes at least one of ethanol and propanol.
[0047] Optionally, the particle size of the mesoporous carbon in the mesoporous carbon suspension is 50-100 nm.
[0048] Optionally, the mass ratio of the modified intermediate to the mesoporous carbon in the mesoporous carbon suspension is 1:(0.8-1.2).
[0049] Optionally, the solid-liquid ratio of the mesoporous carbon in the mesoporous carbon suspension is 0.1-0.2 g / mL.
[0050] Alternatively, the modified intermediate is mixed in a mesoporous carbon suspension at 50-60°C.
[0051] Optionally, the modified intermediate is preheated at 50-60° C. before being mixed with the mesoporous carbon suspension.
[0052] Optionally, after separation, the modified carbon-based negative electrode material is dried at 700-800°C.
[0053] Optionally, the modified carbon-based negative electrode material is prepared by drying for 3-5 hours after separation.
[0054] Optionally, the modified intermediate is surface activated by a nitrogen-containing coupling agent, and then the surface activated modified intermediate is mixed in a mesoporous carbon suspension; wherein the nitrogen-containing coupling agent includes at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, and lauryldimethylamine oxide.
[0055] In a third aspect, the present invention also provides the use of any of the above-mentioned optional modified carbon-based negative electrode materials or modified carbon-based negative electrode materials prepared by any optional preparation method in sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 A flowchart of a method for preparing a modified carbon-based negative electrode material provided by the present invention. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0058] The present invention provides a modified carbon-based negative electrode material, comprising a microporous carbon matrix and a graphene polymer layer and a mesoporous carbon layer sequentially formed on the outside of the microporous carbon matrix. In fact, by forming the graphene polymer layer and the mesoporous carbon layer on the outside of the microporous carbon matrix, the pores gradually decrease, which is beneficial to the penetration of the electrolyte in the negative electrode material, and can effectively alleviate the volume change of sodium ions during the embedding and de-embedding process.
[0059] Specifically, the graphene polymer layer includes a composite skeleton and a carbonized layer that is polymerized and carbonized on the surface of the composite skeleton, and the composite skeleton is formed by a composite of graphene and molybdenum sulfide. In fact, the composite skeleton in the negative electrode material can play a supporting role, which is conducive to separating the microporous carbon matrix from the mesoporous carbon layer. In addition, it can effectively alleviate the volume change of the microporous carbon matrix and the mesoporous carbon layer, and at the same time, it can also connect the microporous carbon matrix with the mesoporous carbon layer, effectively reducing the sodium ion transmission resistance.
[0060] In fact, the molybdenum sulfide in the composite skeleton can significantly improve the flexibility of the composite skeleton, thereby improving the buffering performance of the composite skeleton during volume changes and its own structural stability, and maintaining the overall structural stability of the negative electrode material through its own elastic changes to a certain extent. In addition, the carbonized layer that is polymerized and carbonized on the outside of the composite skeleton is conducive to improving the uniformity of the carbonized layer through polymerization, thereby improving the stability of the molybdenum sulfide in the composite skeleton. At the same time, the carbonized layer also has certain self-repairing properties, which can fill the cracks on the composite skeleton during the volume change process, thereby effectively extending the overall service life and cycle stability of the negative electrode material.
[0061] The present invention also provides a method for preparing a modified carbon-based negative electrode material, comprising: subjecting a microporous carbon matrix to a hydrothermal reaction with nanographene in a sulfur-molybdenum mixed solution and separating and drying to obtain a modified precursor; polymerizing a polymerization monomer on the surface of the modified precursor under the action of an initiator and separating and carbonizing the monomer, and then compounding the monomer with mesoporous carbon to obtain a modified carbon-based negative electrode material.
[0062] In fact, when the microporous carbon matrix is subjected to a hydrothermal reaction with nano-graphene in a sulfur-molybdenum mixed solution, the microporous carbon matrix acts as a forming core structure, which is conducive to the attachment of nano-graphene to the surface of the microporous carbon matrix. In the hydrothermal reaction, the sulfur element reacts with the molybdenum element to generate nano-molybdenum sulfide, and the nano-molybdenum sulfide and nano-graphene are superimposed on the surface of the microporous carbon matrix, thereby forming an initial molybdenum sulfide@graphene composite structure.
[0063] In fact, when separating and drying after the hydrothermal reaction, it is beneficial to remove the moisture attached to the surface of the microporous carbon matrix, and at the same time, the initial molybdenum sulfide @ graphene composite structure can be preformed to obtain a composite skeleton (modified precursor) after preliminary curing, which is beneficial to the polymerization coverage of the polymerization monomer. After carbonization treatment, it is beneficial to improve the bonding tightness between the composite skeleton and the carbonized layer, thereby improving the coating performance of the molybdenum sulfide structure.
[0064] In fact, the approximate structure of the graphene polymer layer is a stacked structure of "graphene-molybdenum sulfide-polymer carbide", so that the molybdenum sulfide can be enclosed between the graphene and the polymer carbide, thereby avoiding exposure and detachment of the molybdenum sulfide during the volume expansion process, thereby avoiding affecting the overall cycle stability and service life of the composite material.
[0065] In some embodiments, see Figure 1 The method for preparing the modified carbon-based negative electrode material provided by the present invention comprises the following steps:
[0066] S1, putting the microporous carbon matrix and nanographene into a sulfur-molybdenum mixed solution to prepare a mixed suspension;
[0067] S2, subjecting the mixed suspension to a hydrothermal reaction, separating the mixed suspension, and drying the mixed suspension at 600-700° C. to obtain a modified precursor;
[0068] S3, mixing the modified precursor with the polymerizable monomer and polymerizing them in situ under the action of an initiator, and then separating and carbonizing to obtain a modified intermediate;
[0069] S4. After mixing the modified intermediate in the mesoporous carbon suspension, separating and drying the modified carbon-based negative electrode material.
[0070] In some embodiments, when executing step S1, pre-mixing the microporous carbon matrix and nano-graphene in the sulfur-molybdenum mixed solution is beneficial to improving the dispersion uniformity of the microporous carbon matrix and nano-graphene in the sulfur-molybdenum mixed solution, thereby enabling the nano-graphene to be uniformly attached to the surface of the microporous carbon matrix, thereby avoiding uneven uniformity of the composite skeleton formed on the surface of the modified precursor.
[0071] In some embodiments, when performing step S1, after the microporous carbon matrix and nanographene are put into the sulfur-molybdenum mixed solution, physical dispersion can be used to make the microporous carbon matrix and nanographene uniformly dispersed in the sulfur-molybdenum mixed solution. Specifically, the physical dispersion means used can include at least one of ultrasonic dispersion, oscillation dispersion, and stirring dispersion. In fact, it is preferred to use ultrasonic dispersion, so that the agglomeration and sedimentation of the microporous carbon matrix and nanographene can be avoided by the cavitation effect brought by ultrasonic dispersion.
[0072] In some embodiments, when performing step S1, the mass ratio of the microporous carbon matrix to the nanographene is 1:(0.5-0.6). In fact, by regulating the mass ratio of the microporous carbon matrix to the nanographene, the molding thickness of the nanographene on the surface of the microporous carbon matrix can be controlled, which is conducive to controlling the thickness of the composite skeleton on the surface of the microporous carbon matrix. In fact, when the content of nanographene is too low, it is easy to cause the nanographene distribution uniformity on the surface of the microporous carbon matrix to be poor, and when the content of nanographene is too high, it is easy to form an overly thick composite skeleton, thereby affecting the mitigation performance of volume expansion.
[0073] In some embodiments, when performing step S1, the particle size of the microporous carbon matrix is 500-800nm, and the particle size of the nanographene is 200-300nm. Ultrasonic mixing of the microporous carbon matrix with the nanographene in these two different particle size ranges is beneficial to uniformly disperse the nanographene on the surface of the microporous carbon matrix and form a controllable composite skeleton. Specifically, when performing step S1, the microporous carbon matrix can be prepared by hydrothermal method on sucrose solution, and after the microporous carbon matrix is obtained, it is centrifuged, washed and dried.
[0074] In some embodiments, when executing step S1, the microporous carbon matrix and nanographene are ground and premixed in advance, and then the premixed substances are added to the sulfur-molybdenum mixed solution. In fact, by premixing the microporous carbon matrix and nanographene, it is beneficial to increase the active sites on the surface of the microporous carbon matrix, and at the same time, the nanographene can be pre-combined on the surface of the microporous carbon matrix, which is beneficial to improve the uniformity of the nanographene on the surface of the microporous carbon matrix.
[0075] In fact, before executing step S1, the microporous carbon matrix can be pre-treated with a nitrogen-containing activator for surface activation, which can greatly increase the active sites on the surface of the microporous carbon matrix, thereby facilitating the coating of nanographene on the surface of the microporous carbon matrix. In addition, the nitrogen-containing activator can also introduce nitrogen atoms into the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.
[0076] Specifically, the nitrogen-containing active agent includes at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, and lauryldimethylamine oxide. In fact, before executing step S1, other types of active agents can also be used to activate the surface of the microporous carbon matrix. When the surface is treated with active agents containing different heteroatoms, different electrochemical properties can be given to the negative electrode material.
[0077] In some embodiments, when performing step S1, the solute in the sulfur-molybdenum mixed solution used includes at least thiourea and sodium molybdate. In fact, by adjusting the type of solute in the sulfur-molybdenum mixed solution, the efficiency of molybdenum sulfide generated in the hydrothermal reaction can be controlled. Specifically, the molar ratio of sulfur element to molybdenum element in the sulfur-molybdenum mixed solution is 2: (1-2), which is conducive to the rapid generation of nano-molybdenum sulfide in the hydrothermal reaction.
[0078] In fact, by controlling the generation efficiency of molybdenum sulfide during the hydrothermal reaction, the morphology of the "nanographene-nanomolybdenum sulfide" composite stacked structure generated on the surface of the microporous carbon matrix can be regulated, thereby regulating the electrochemical properties of the composite skeleton.
[0079] In some embodiments, after performing step S1, the mass ratio of nanographene to sulfur in the mixed suspension is 1:(1-1.5). In fact, by regulating the mass ratio of nanographene to sulfur, the composition of the composite skeleton can be controlled. Specifically, the solid-liquid ratio of nanographene to the microporous carbon matrix as a whole in the mixed suspension is 0.1-0.2 g / mL. Controlling the solid-liquid ratio is beneficial for uniform coverage of nano-molybdenum sulfide on the surface of the microporous carbon matrix during the hydrothermal reaction, thereby obtaining a composite skeleton in which molybdenum sulfide and graphene are uniformly dispersed.
[0080] In some embodiments, after performing step S1, the pH of the mixed suspension is adjusted to 6-7 using a pH regulator or a buffer solution, and the mixed suspension is kept warm at 40-50° C. In fact, the warming process is conducive to the pre-binding of nanographene in the mixed suspension on the surface of the microporous carbon matrix, and the weakly acidic and neutral mixed suspension is conducive to the generation of nano-molybdenum sulfide in the subsequent hydrothermal reaction.
[0081] Specifically, when performing step S2, the mixed suspension is subjected to a hydrothermal reaction at 200-220°C, thiourea is decomposed at high temperature to generate hydrogen sulfide, and hydrogen sulfide as a reducing agent can reduce molybdate ions in sodium molybdate to molybdenum ions, and generate nano-molybdenum sulfide with sulfur atoms. In fact, the hydrothermal reaction carried out at different temperatures will greatly affect the morphology of nano-molybdenum sulfide formed on the surface of the microporous carbon matrix, and the nano-molybdenum sulfide generated at 200-220°C is conducive to compounding with nano-graphene to generate a composite skeleton.
[0082] Specifically, when executing step S2, the mixed suspension is subjected to a hydrothermal reaction at 3-5 MPa. In fact, when the reaction is carried out under a high-pressure environment, it is beneficial to the temperature rise of the hydrothermal reaction. In addition, it is also beneficial to the decomposition of thiourea under a high-pressure environment, thereby maintaining the continuous progress of the hydrothermal reaction. At the same time, the reaction under high pressure is also beneficial to the dispersion of nano-graphene and microporous carbon matrix in the mixed suspension and the crystallization of nano-molybdenum sulfide.
[0083] In some embodiments, when executing step S2, the mixed suspension is hydrothermally reacted under hydrothermal conditions for 18-24 hours. By controlling the hydrothermal reaction time, it is beneficial to the uniform generation of nano-molybdenum sulfide on the surface of the microporous carbon matrix. In addition, it is also beneficial to the uniform composite of nano-molybdenum sulfide and nano-graphene, thereby improving the comprehensive performance of the generated composite skeleton.
[0084] In some embodiments, when executing step S2, the mixed suspension is cooled to 50-70°C after the hydrothermal reaction and then separated, which is conducive to the full reaction of sodium molybdate and thiourea, and is also conducive to the formation of nano sodium molybdate on nano graphene. Specifically, common physical separation means such as filtration separation and suction filtration separation can be used during separation. In fact, after separation, deionized water and anhydrous ethanol can be used for circulating flushing, which is conducive to removing the loose nano molybdenum sulfide and nano graphene on the surface, thereby improving the overall stability of the composite skeleton.
[0085] In some embodiments, when executing step S2, an organic ligand is pre-dissolved in the mixed suspension. The addition of the organic ligand is helpful to act as an adhesive to fix the nano-graphene, the microporous carbon matrix and the in-situ generated nano-molybdenum sulfide, thereby improving the overall stability of the composite skeleton.
[0086] In fact, the organic ligands include 2-(5-bromo-2-pyridyl azo)-5-(diethylamino) phenol and hydroxylamine. Since hydroxylamine has a certain reducing property, it is beneficial to accelerate the reaction rate between sodium molybdate and thiourea, thereby promoting more nano-molybdenum sulfide to adhere to the surface of the microporous carbon matrix per unit time. In addition, 2-(5-bromo-2-pyridyl azo)-5-(diethylamino) phenol and hydroxylamine can also react with the active groups on the surface of the microporous carbon matrix, which is beneficial to anchor the nano-graphene, thereby effectively improving the connection strength between the composite skeleton and the microporous carbon matrix.
[0087] In some embodiments, when performing step S2, the solid separated after the hydrothermal reaction is heated to 600-700°C at a rate of 1-10°C / min. In fact, high-temperature drying is beneficial to composite and fix nano-graphene and nano-molybdenum sulfide, so that a modified precursor with a stable structure can be obtained. Specifically, the obtained solid is dried in a vacuum environment at 600-700°C for 3-5h. Specifically, during the drying process, the composite skeleton on the surface of the microporous carbon matrix is inevitably prone to collapse, which is beneficial to increase the specific surface area and surface activity of the modified precursor.
[0088] In fact, when executing step S3, the mass ratio of the modified precursor to the polymerized monomer is 1:(0.4-0.5). Specifically, by regulating the mass of the polymerized monomer, the polymerization thickness of the polymerized monomer after polymerization on the surface of the composite skeleton can be adjusted, thereby preventing the polymerized layer on the surface of the composite skeleton from blocking the pore structure of the composite skeleton after carbonization, and also preventing the polymerized monomer from being polymerized too much outside the composite skeleton to avoid affecting the subsequent composite with the mesoporous carbon layer.
[0089] Specifically, when executing step S3, when the amount of polymerization monomer used is too small, it will cause difficulty in uniformly polymerizing the polymerization monomer in the composite skeleton, thereby affecting the coating protection performance of the composite skeleton. When the amount of polymerization monomer used is too large, it will affect the pore size of the composite skeleton, thereby affecting the adaptability of the composite skeleton to volume changes.
[0090] In some embodiments, when executing step S3, the polymerizable monomers may be dissolved to form a polymer solution, and then the modified precursor may be mixed and dispersed in the polymer solution, which is conducive to uniform mixing of the polymerizable monomers and the modified precursor, thereby enabling the polymerizable monomers to perform in-situ polymerization on the surface with the modified precursor as the core. In fact, the solvent in the polymer solution may be any solvent that can dissolve the polymerizable monomers and the initiator and does not react with the polymerizable monomers and the modified precursor.
[0091] Specifically, when performing step S3, the polymerized monomer includes at least one of pyrrole, aniline, thiophene, and acrylonitrile. In fact, when pyrrole is in situ polymerized on the surface of the modified precursor, a polypyrrole layer can be formed on the surface of the composite skeleton. Specifically, by selecting different polymerized monomers, different polymer structures can be formed on the composite skeleton, and then after carbonization, carbonized layers with different densities and different heteroatom doping can be obtained.
[0092] In some embodiments, when performing step S3, the initiator includes at least one of ammonium persulfate, azobisisobutyronitrile, and dibenzoyl peroxide. In fact, the mass ratio of the initiator to the polymerization monomer is (0.1-5):100. By controlling the amount of the initiator, the polymerization reaction initiation effect can be achieved, and the introduction of too much initiator to avoid affecting the negative electrode material itself.
[0093] In some embodiments, when executing step S3, an in-situ polymerization reaction is carried out under the action of an initiator and the temperature of the reaction environment is controlled to be 40-50°C, which is conducive to the reaction of the polymerization monomer on the surface of the modified precursor, thereby improving the uniformity of the formation of the polymer layer on the surface of the composite skeleton. In fact, after the solids after the in-situ polymerization reaction are separated, they are transferred to an atmosphere furnace at 700-800°C for high-temperature carbonization treatment to obtain a modified intermediate, so that the polymer layer can be converted into a carbonized layer and coated on the surface of the composite skeleton.
[0094] In some embodiments, when performing step S4, the particle size of the mesoporous carbon in the mesoporous carbon suspension is 50-100 nm. In fact, the small-particle mesoporous carbon is dispersed on the surface of the modified intermediate, which is conducive to the overall coating of the outer side of the composite skeleton, thereby forming a mesoporous carbon layer. In fact, the liquid environment in the mesoporous carbon suspension includes at least one of ethanol and propanol.
[0095] Specifically, when executing step S4, functional additives such as active agents and dispersants may be dissolved in the mesoporous carbon suspension to improve the dispersibility of the mesoporous carbon in the mesoporous carbon suspension, or high-frequency ultrasound may be applied to the mesoporous carbon suspension to promote uniform dispersion of the mesoporous carbon in the mesoporous carbon suspension.
[0096] In some embodiments, when performing step S4, the mass ratio of the modified intermediate to the mesoporous carbon in the mesoporous carbon suspension is 1:(0.8-1.2), which is conducive to the uniform dispersion of the mesoporous carbon on the surface of the modified intermediate, thereby promoting the mesoporous carbon to form a uniform mesoporous carbon layer on the surface of the modified intermediate. Specifically, the solid-liquid ratio of the mesoporous carbon in the mesoporous carbon suspension is 0.1-0.2 g / mL, which is conducive to the uniform dispersion of the mesoporous carbon and the modified intermediate in the suspension.
[0097] In some embodiments, when performing step S4, the modified intermediate is preheated at 50-60°C before being mixed with the mesoporous carbon suspension, which can improve the surface activity of the modified intermediate and promote the coating molding of the mesoporous carbon on the surface of the modified intermediate. In fact, when performing step S4, the mesoporous carbon suspension can be preheated in a water bath at 50-60°C for insulation.
[0098] In some embodiments, when performing step S4, the modified intermediate is pre-surface activated by using a nitrogen-containing coupling agent, and then the modified intermediate after surface activation is dispersed in a mesoporous carbon suspension, which is beneficial to improve the coating efficiency of mesoporous carbon on the surface of the modified intermediate. Specifically, the nitrogen-containing coupling agent includes at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, and lauryldimethylamine oxide.
[0099] In some embodiments, when performing step S4, after the modified intermediate is mixed in the mesoporous carbon suspension, the uncoated mesoporous carbon is filtered and sieved to remove the solid, and the obtained solid is dried and sintered at 700-800°C, so that the mesoporous carbon on the surface of the modified intermediate is solidified and formed, which is beneficial to improve the overall structural stability of the negative electrode material. Specifically, the obtained solid is dried at 700-800°C for 3-5h and then cooled to room temperature to obtain a modified carbon-based negative electrode material.
[0100] The present invention also provides an application of the modified carbon-based negative electrode material provided in any of the above embodiments in a sodium ion battery. Specifically, the modified carbon-based negative electrode material can be blended with a binder and a conductive agent to prepare a negative electrode for a sodium ion battery.
[0101] Example 1
[0102] This embodiment 1 provides a method for preparing a modified carbon-based negative electrode material, comprising the following steps:
[0103] S1. A microporous carbon matrix with an average particle size of 600 nm and nanographene with an average sheet size of 200 nm (purchased from Beijing Graphene Research Institute Co., Ltd., with an average specific surface area of 500 m 2 / g) in a mass ratio of 1:0.5, using zirconium oxide as a grinding ball in a ball mill, pre-milling for 15 minutes at a ball-to-material ratio of 15:1, and then the pre-mixed mixture is added into a sulfur-molybdenum mixed solution (the molar ratio of sulfur element to molybdenum element is 1:1, and the mass ratio of nanographene to sulfur element is 1:1.2, and the solvent is deionized water) containing thiourea and sodium molybdate at a solid-liquid ratio of 0.15g / L, and ultrasonically treated at a frequency of 20kHz for 10min, and the pH is adjusted to 7.0 and then kept warm in a 45℃ water bath environment for 1h to obtain a mixed suspension;
[0104] S2. The mixed suspension is transferred to a hydrothermal reactor, the atmosphere in the hydrothermal reactor is adjusted to 4 MPa of nitrogen, and the hydrothermal reactor is controlled to perform a hydrothermal reaction on the mixed suspension at 200° C. for 20 hours. The mixed suspension is naturally cooled to 60° C., and then the mixed suspension is taken out, and after separation by suction filtration, the solid obtained by suction filtration is cyclically rinsed with deionized water and anhydrous ethanol. After cyclic rinsing three times, the solid is transferred to a vacuum drying oven, and the temperature is increased to 700° C. at a heating rate of 5° C. / min, and the modified precursor is obtained after the temperature is kept at 700° C. for 4 hours and the solid weight is constant;
[0105] S3, preheating the modified precursor in an air atmosphere at 45°C for 1 hour, then adding the preheated modified precursor to a pyrrole solution (the mass ratio of the modified precursor to pyrrole is 1:0.4, and the solvent is anhydrous ethanol) kept warm in a water bath at 45°C, ultrasonically mixing at a frequency of 20kHz for 10 minutes, and then dropping an ammonium persulfate solution (the mass ratio of ammonium persulfate to pyrrole is 3:100, and the solvent is deionized water) dropwise into the pyrrole solution, controlling the total dropping time to be 30 minutes, stirring and mixing during the dropping process, keeping warm and stirring the reaction for 2 hours after the dropping is completed, and then filtering and separating, washing the filtered solid with anhydrous ethanol and drying it in a hot air drying oven at 80°C to constant weight, and transferring the dried solid to a 750°C atmosphere furnace, carbonizing it for 2 hours under a nitrogen atmosphere, and then cooling it to room temperature with the furnace to obtain a modified intermediate;
[0106] S4. After preheating the modified intermediate in a drying oven at 55°C, add the preheated modified intermediate into a mesoporous carbon suspension with a solid-liquid ratio of 0.15 g / mL in a water bath at 55°C (the average particle size of the mesoporous carbon is 100 nm, the average pore size is 4.43 nm, purchased from Jiangsu Xianfeng Nanomaterials Co., Ltd., No. XFP12; the liquid environment is anhydrous ethanol; the mass ratio of the modified intermediate to the mesoporous carbon is 1:1), and ultrasonically disperse at a frequency of 20 kHz for 10 minutes. After stirring and reacting for 1 hour in a water bath at 55°C, filter and separate to remove the uncoated mesoporous carbon, and then dry the obtained solid in a 750°C atmosphere furnace under a nitrogen atmosphere for 4 hours and keep constant weight, and then cool to room temperature with the furnace to obtain a modified carbon-based negative electrode material.
[0107] Example 2
[0108] This embodiment 2 provides a method for preparing a modified carbon-based negative electrode material, which is different from the embodiment 1 in that, when executing step S1, the microporous carbon matrix and hexadecyltrimethylammonium chloride are mixed in a mass ratio of 1:0.2 in advance, put into ethanol, stirred to dissolve and mix, and then ultrasonically treated at a frequency of 20 kHz for 15 minutes, filtered, rinsed with anhydrous ethanol, and transferred to a 80°C hot air drying oven to dry to constant weight.
[0109] Example 3
[0110] This embodiment 3 provides a preparation method of a modified carbon-based negative electrode material, which is different from embodiment 2 in that, when executing step S4, the modified intermediate and hexadecyltrimethylammonium chloride are mixed in a mass ratio of 1:0.2 in advance, put into ethanol, stirred to dissolve and mix, and then ultrasonically treated at a frequency of 20 kHz for 15 minutes, filtered, rinsed with anhydrous ethanol, and transferred to a 80°C hot air drying oven to dry to constant weight.
[0111] Example 4
[0112] This embodiment 4 provides a method for preparing a modified carbon-based negative electrode material, which is different from embodiment 3 in that, when executing step S2, 2-(5-bromo-2-pyridylazo)-5-(diethylamino)phenol (CAS: 14337-53-2) and hydroxylamine (CAS: 7803-49-8) are mixed and dissolved in ethanol in a mass ratio of 1:1 to prepare a polymerization solution, and the polymerization solution and the mixed suspension are stirred and mixed and then transferred to a hydrothermal reactor; wherein the mass ratio of hydroxylamine to nano-graphene in the hydrothermal reactor is 1:20.
[0113] Comparative Example 1
[0114] This comparative example 1 provides a method for preparing a modified carbon-based negative electrode material, which is different from Example 1 in that step S3 and step S4 are not performed, and the modified carbon-based negative electrode material is prepared in step S2.
[0115] Comparative Example 2
[0116] This comparative example 2 provides a method for preparing a modified carbon-based negative electrode material, which is different from Example 1 in that step S4 is not performed, and the modified carbon-based negative electrode material is obtained in step S3.
[0117] Comparative Example 3
[0118] This comparative example 3 provides a method for preparing a modified carbon-based negative electrode material, which is different from Example 1 in that step S3 is not performed, and the modified precursor prepared in step S2 is subjected to step S4 to prepare the modified carbon-based negative electrode material.
[0119] Performance Testing
[0120] The modified carbon-based negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used as active materials, mixed with sodium carboxymethyl cellulose and acetylene black in a ratio of 90:5:5, and coated on the current collector copper foil, vacuum dried and rolled into a composite sheet, which was cut into a circular electrode sheet with a diameter of 10 mm, metallic sodium was used as the counter electrode and reference electrode, sodium hexafluorophosphate was used as the electrolyte, and assembled into CR2032 button batteries in an argon atmosphere glove box, and the following tests were performed:
[0121] First coulombic efficiency test: at room temperature, discharge at a constant current of 0.1C to 0.01V, then discharge at a constant current of 0.02C to 0.005V, and finally charge at a constant current of 0.1C to 2.0V. The capacity when charged to 2.0V is measured as the first reversible specific capacity, and the first coulombic efficiency is calculated. The results are shown in Table 1.
[0122] Cycle performance test: constant current charge and discharge were performed at room temperature with a current density of 0.1C, the charge and discharge voltage was limited to 0.005-2.0V, and the charge specific capacity after 100 cycles was measured, and the capacity retention rate after 100 cycles was calculated. The results are shown in Table 1.
[0123] Table 1
[0124] First reversible specific capacity (mAh / g) First coulombic efficiency (%) Charge specific capacity (after 100 cycles, mAh / g) Capacity retention rate (after 100 cycles, %) Example 1 415 86 374 90.12 Example 2 431 87 395 91.64 Example 3 438 88 405 92.47 Example 4 446 90 418 93.72 Comparative Example 1 376 80 325 85.44 Comparative Example 2 384 84 339 88.28 Comparative Example 3 392 82 341 86.99
[0125] Combining Example 1 and Example 2, it can be seen from Table 1 that when Example 2 is preparing the negative electrode material, the microporous carbon matrix is pre-activated with a nitrogen-containing activator in step S1, which can effectively increase the number of active sites on the surface of the microporous carbon matrix, thereby promoting the loading of nanographene on the surface of the microporous carbon matrix, and at the same time, nitrogen atoms are introduced between the bonding interface layer between the nanographene and the microporous carbon matrix for doping. Therefore, compared with Example 1, the battery prepared by the modified carbon-based negative electrode material in Example 2 has higher capacity and cycle stability.
[0126] In combination with Example 2 and Example 3, it can be seen from Table 1 that when Example 3 is preparing the negative electrode material, the modified intermediate is pre-activated with a nitrogen-containing active agent in step S4, which can further increase the content of nitrogen atoms in the carbon-based negative electrode material, and is beneficial to the loading and coating of mesoporous carbon in the modified intermediate, thereby improving the structural stability of the mesoporous carbon layer in the carbon-based negative electrode material. Compared with Example 2, the battery prepared by the modified carbon-based negative electrode material in Example 3 has higher capacity and cycle stability.
[0127] It can be seen from Examples 1 to 3 that doping with nitrogen atoms in the modified carbon-based negative electrode material can further improve the electrochemical properties of the negative electrode material. It can be seen from Table 1 that both the capacity performance and the cycle stability can be improved. This is because nitrogen atoms enter the connecting interface layer between the microporous carbon matrix and the graphene polymer layer, and between the graphene polymer layer and the mesoporous carbon layer, which can improve the interface stability and structural toughness, and help reduce the separation and rupture of the interface layers during volume expansion.
[0128] Combining Example 3 with Example 4, it can be seen from Table 1 that when Example 4 is preparing the negative electrode material, 2-(5-bromo-2-pyridyl azo)-5-(diethylamino)phenol and hydroxylamine are added in step S2, so that when the hydrothermal reaction is performed to generate nano-molybdenum sulfide, it is beneficial to anchor the nano-molybdenum sulfide, and at the same time, the loading amount of nano-molybdenum sulfide on the surface of nano-graphene can be increased. In addition, after calcination and carbonization at 700°C, the nano-molybdenum sulfide can be coated and protected, thereby effectively improving the stability of the nano-molybdenum sulfide when the volume of the negative electrode material expands. Compared with Example 3, the battery prepared by using the modified carbon-based negative electrode in Example 4 has a higher capacity and more outstanding cycle stability.
[0129] In combination with Example 1 and Comparative Example 1, it can be seen from Table 1 that when the negative electrode material is prepared in Comparative Example 1, step S3 and step S4 are not performed, so that most of the nano-molybdenum sulfide on the surface of the negative electrode material in Comparative Example 1 is in an exposed state, and the outer layer is not coated with mesoporous carbon, which greatly reduces the capacity of the negative electrode material. In addition, the nano-molybdenum sulfide on the surface is prone to fall off during a long cycle, resulting in a significant decrease in structural stability.
[0130] Combining Comparative Example 1 and Comparative Example 2, it can be seen from Table 1 that when Comparative Example 2 is preparing the negative electrode material, by performing step S3 to coat the surface of the nano-molybdenum sulfide on the graphene surface with a carbon structure, the stability of the nano-molybdenum sulfide can be improved, thereby facilitating the improvement of the structural stability of the negative electrode material during a long cycle, and thus improving the capacity retention rate of the battery. In addition, it can be seen from Example 1, Comparative Example 1 to Comparative Example 2 that the stability of the graphene polymer layer and the stability of the nano-molybdenum sulfide are strongly correlated with the capacity stability of the battery.
[0131] Combining Comparative Examples 1 to 3, it can be seen from Table 1 that when the negative electrode material is prepared in Comparative Example 3, when the mesoporous carbon is directly coated on the surface of the modified precursor, since the nano-molybdenum sulfide is not coated and fixed, the nano-molybdenum sulfide is easily fallen off during the mesoporous carbon coating, thereby reducing the content of nano-molybdenum sulfide in the negative electrode material. At the same time, during the use of the negative electrode material assembled into a battery, when the volume of the negative electrode material expands, the nano-molybdenum sulfide is very easy to fall off from the graphene, thereby reducing the capacity stability. However, compared with Comparative Example 1, the capacity stability of Comparative Example 3 is relatively high, but significantly inferior to Comparative Example 2.
[0132] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A modified carbon-based negative electrode material for a sodium ion battery, characterized in that: It includes a microporous carbon matrix and a graphene polymerization layer and a mesoporous carbon layer sequentially formed on the outside of the microporous carbon matrix. The graphene polymerization layer includes a composite skeleton and a carbonized layer polymerized and carbonized on the surface of the composite skeleton, and the composite skeleton is formed by the composite of graphene and molybdenum sulfide.
2. A method for preparing a modified carbon-based negative electrode material as claimed in claim 1, characterized in that: include: The microporous carbon matrix is subjected to hydrothermal reaction with nanographene in a sulfur-molybdenum mixed solution and separated, and dried at 600°C-700°C to obtain a modified precursor. Under the action of an initiator, the polymerization monomer is polymerized on the surface of the modified precursor and separated and carbonized, and then compounded with mesoporous carbon to obtain a modified carbon-based negative electrode material; the solute of the sulfur-molybdenum mixed solution includes at least thiourea and sodium molybdate.
3. The preparation method according to claim 2, characterized in that: The following steps are involved: Putting the microporous carbon matrix and nanographene into a sulfur-molybdenum mixed liquid to prepare a mixed suspension; The mixed suspension is separated after hydrothermal reaction and dried at 600-700° C. to obtain a modified precursor; The modified precursor is mixed with the polymerizable monomer, and then in situ polymerized under the action of an initiator, and then separated and carbonized to obtain a modified intermediate; The modified intermediate is mixed in a mesoporous carbon suspension, and then separated and dried to obtain a modified carbon-based negative electrode material.
4. The preparation method according to claim 2, characterized in that: The microporous carbon matrix is surface activated by using a nitrogen-containing active agent, wherein the nitrogen-containing active agent includes at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride and lauryldimethylamine oxide.
5. The preparation method according to claim 3, characterized in that: The mass ratio of microporous carbon matrix to nanographene is 1:(0.5-0.6); and / or, the particle size of the microporous carbon matrix is 500-800 nm; And / or, the particle size of nanographene is 200-300nm; and / or, the molar ratio of sulfur element to molybdenum element in the sulfur-molybdenum mixed solution is 2:(1-2); and / or, the mass ratio of nanographene to sulfur in the mixed suspension is 1:(1-1.5); and / or, the solid-to-liquid ratio in the mixed suspension is 0.1-0.2 g / mL; And / or, grinding and premixing the microporous carbon matrix and nanographene and then adding them into the sulfur-molybdenum mixed solution; and / or, after the microporous carbon matrix and the nanographene are put into the sulfur-molybdenum mixed solution, a mixed suspension is prepared under physical dispersion, wherein the physical dispersion includes at least one of ultrasonic dispersion, oscillation dispersion, and stirring dispersion; and / or, keeping the mixed suspension at 40-50° C.; And / or, adjusting the pH of the mixed suspension to 6-7.
6. The preparation method according to claim 3, characterized in that: The mixed suspension is subjected to a hydrothermal reaction at 200-220°C; and / or, subjecting the mixed suspension to a hydrothermal reaction for 18-24 hours; and / or, subjecting the mixed suspension to a hydrothermal reaction at 3-5 MPa; And / or, an organic ligand is also dissolved in the mixed suspension, and the organic ligand includes 2-(5-bromo-2-pyridyl azo)-5-(diethylamino)phenol and hydroxylamine; and / or, subjecting the mixed suspension to a hydrothermal reaction and then cooling it to 50-70° C. before separation; And / or, when the mixed suspension is subjected to a hydrothermal reaction and then separated, the separation method comprises one of filtration separation and suction filtration separation; and / or, after the mixed suspension is subjected to hydrothermal reaction and separated, it is circulated and rinsed with deionized water and anhydrous ethanol; and / or, drying in a vacuum environment at 600-700° C. to obtain a modified precursor; and / or, drying at 600-700° C. for 3-5 hours to obtain a modified precursor; And / or, after the mixed suspension is subjected to hydrothermal reaction and separated, the separated solid is heated to 600-700° C. at a rate of 1-10° C. / min.
7. The preparation method according to claim 3, characterized in that: The mass ratio of the modified precursor to the polymerized monomer is 1:(0.4-0.5); and / or, the polymerizable monomer includes at least one of pyrrole, aniline, thiophene and acrylonitrile; and / or, the initiator comprises at least one of ammonium persulfate, azobisisobutyronitrile, and dibenzoyl peroxide; and / or, the mass ratio of the initiator to the polymerization monomer is (0.1-5):100; and / or, after dissolving the polymerizable monomer to prepare a polymer solution, the modified precursor is mixed and dispersed in the polymer solution; and / or, in situ polymerization of the polymerizable monomers on the surface of the modified precursor at 40-50° C. under the action of an initiator; And / or, after in-situ polymerization under the action of an initiator and separation, carbonization is performed at 700-800°C to obtain a modified intermediate.
8. The preparation method according to claim 3, characterized in that: The liquid environment in the mesoporous carbon suspension includes at least one of ethanol and propanol; and / or, the particle size of the mesoporous carbon in the mesoporous carbon suspension is 50-100 nm; and / or, the mass ratio of the modified intermediate to the mesoporous carbon in the mesoporous carbon suspension is 1:(0.8-1.2); and / or, the solid-liquid ratio of the mesoporous carbon in the mesoporous carbon suspension is 0.1-0.2 g / mL; and / or, mixing the modified intermediate in a mesoporous carbon suspension at 50-60° C.; and / or, drying at 700-800° C. after separation to obtain a modified carbon-based negative electrode material; And / or, drying for 3-5 hours after separation to obtain a modified carbon-based negative electrode material.
9. The preparation method according to claim 3, characterized in that: After the modified intermediate is surface activated by a nitrogen-containing coupling agent, the surface activated modified intermediate is mixed in a mesoporous carbon suspension; wherein the nitrogen-containing coupling agent comprises at least one of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride and lauryldimethylamine oxide.
10. Use of the modified carbon-based negative electrode material according to claim 1 or the modified carbon-based negative electrode material prepared by the preparation method according to any one of claims 2 to 9 in a sodium ion battery.
Citation Information
Patent Citations
Sodium-ion battery carbon negative electrode material and preparation method thereof
CN105870425A
Preparation method for graphene-molybdenum disulfide-polyaniline ternary composite electrode material
CN106887347A